Enabling Environments? A Spotlight on Community Mental Health Team Offices in Wales - Oliver John; Shane Mills; Adrian Clarke; Alka Ahuja; Dafydd Huw (BJPsych Open)
Aims: A CMHT office should provide a comfortable, supportive, and therapeutic environment for staff and visitors. It should be accessible and welcoming, it should support the development and maintenance of good relationships, recognition of boundaries and make staff and service users feel physically and emotionally safe.